Coherence based graph convolution network for motor imagery-induced EEG after spinal cord injury - Li, Han; Liu, Ming; Yu, Xin; Zhu, JianQun; Wang, Chongfeng; Chen, Xinyi; Feng, Chao; Leng, Jiancai; Zhang, Yang; Xu, Fangzhou (Frontiers in Neuroscience, 2023)
Background Spinal cord injury (SCI) may lead to impaired motor function, autonomic nervous system dysfunction, and other dysfunctions. Brain-computer Interface (BCI) system based on motor imagery (MI) can provide more scientific and effective treatment solutions for SCI patients. Methods According to the interaction between brain regions, a coherence-based graph convolutional network (C-GCN) method is proposed to extract the temporal-frequency-spatial features and functional connectivity information of EEG signals. The proposed algorithm constructs multi-channel EEG features based on coherence networks as graphical signals and then classifies MI tasks. Different from the traditional graphical convolutional neural network (GCN), the C-GCN method uses the coherence network of EEG signals to determine MI-related functional connections, which are used to represent the intrinsic connections between EEG channels in different rhythms and different MI tasks. EEG data of SCI patients and healthy subjects have been analyzed, where healthy subjects served as the control group. Results The experimental results show that the C-GCN method can achieve the best classification performance with certain reliability and stability, the highest classification accuracy is 96.85%. Conclusion The proposed framework can provide an effective theoretical basis for the rehabilitation treatment of SCI patients.